Pirólise de Spirulina maxima: valores de energia de ativação e catálise in-situ aumentando a seletividade para hidrocarbonetos aromáticos - Simão, Bárbara Lopes (2017)
The use of microalgae and cyanobacteria as an important source for biofuels and value-added chemicals has been widely reported as a promising sustainable technology. As a result of this fact, renewable energy sources, such as biomass, have a fundamental importance in the energy, environment and socioeconomic context. Due to they are among the fastest growing photosynthetic microorganisms, they also have the ability to easily adapt to various climatic conditions and have high efficiency in fixing CO2. A Spirulina maxima is considered a potential raw material for fast pyrolysis due to its low lipid and high protein contents. Aromatic hydrocarbons, which are widely used in industry, are the main derivatives of protein pyrolysis. In this study, thermogravimetric analyses were performed and the activation energy values for biomass thermal degradation were identified using three methodologies: the Friedman and the Flynn-Wall-Ozawa isoconversional methods, and the Miura-Maki distributed activation energy model. The three methodologies resulted in similar mean values of activation energy, namely, 132.2, 143.77 and 130.04 kJ/mol, respectively, for the Flynn-Wall-Ozawa, Friedman and Miura-Maki models. The micropyrolysis of the pure biomass was analyzed at three different reaction temperatures (450, 550 and 650°C) and the composition of the vapor products was evaluated. The micropyrolysis performed at 650°C presented the highest yield of aromatic hydrocarbons and a decrease in oxygenated compounds. In addition, the heating rate was also varied in 1, 5, 10, 15, and 20 ° C / ms, and the composition of the vapors products was evalueted, it can be observed that there were no significant changes when the heating rate varied. Another parameter analyzed was the reaction time, analyzes were performed at three different reaction times (10, 20 and 30). So the composition of the vapors products generated was analyzed, with the increase of reaction time there was a decrease of the oxygenated compounds, however, there were no significant changes in the aromatic compounds. A Spirulina maxima was also subjected to catalytic micropyrolysis by the addition of two types of acid catalysts: zeolite ZSM-5 and niobic acid (HY-340). Under the conditions of this study, the addition of zeolite to microalgae yielded significant results in the production of aromatic hydrocarbons, i.e., the production volume was more than five-fold greater with the biomass-to-catalyst ratio of 1:10 than with the pure biomass. The catalytic effect of the niobium-based catalyst (HY-340) on the production of aromatic compounds was negligible. The niobium is little explored as a catalyst for biomass’s pyrolysis, but it is promising for studies, due to the niobium present high acidity and a significantly lower cost than the commercial zeolites. It is important to emphasize that the data collected in this work can be useful for reactor projects.